Efektivitas model pembelajaran controversial public issues dalam meningkatkan critical thinking skills pada mata pelajaran ekonomi - Rahmayanti, Dhita Aulia; Munir, Syahrul (Jurnal Indovisi, 2024)
The research aims to find out how the Controversial Public Issues (CPI) model in improving the critical thinking skills of students in achieving the dimensions in Profil Pelajar Pancasila of economics subjects. Quasy experiments were used in this research, with XI IPS 2 class subjects as experimental classes and XI IPS 5 as control classes. The results of the N-Gain score showed that the average critical thinking skills score of students using the Controversial Public Issues (CPI) model was higher at 72.14 in the category quite effective compared to students using discovery learning strategies of 36.26 into ineffective categories. The public issues controversial learning model is effective to help improve critical thinking skills. In the Independent Samples T-test, a significance level of 0.000 < 0.05 (significant value), H0 was rejected, which meant that There is a significant difference in the critical thinking skills dimension in the Profil Pelajar Pancasila of students in XI IPS economics subjects through the implementation of the Controversial Public Issues learning model. So, because of Controversial Public Issues models can increase the dimension of critical thinking skills, they can reach the dimensions contained in the Profil Pelajar Pancasila as a transition to implementing the Kurikulum Merdeka.